The Personal Property Securities Act 2009 (Cth) - Where is the fraud exception? - Widdup, Linda (Canterbury Law Review Trust Board, 2017)
Torrens system legislation promotes the principle of indefeasibility of title by upholding the conclusiveness of the land titles register. Nevertheless, fraud on the part of a registered proprietor is specified by the legislation as an exception to indefeasibility. Courts have also recognised exceptions in the form of in personam claims founded in law or equity. A register is also central to personal property securities legislation (PPS legislation). Priority between competing security interests in personal property is normally dictated by registration. The priority rules are comprehensive which compels the conclusion that any priority dispute between security interests will be decided within the four walls of the statute. Yet PPS legislation does not contain a specific carve out for fraud. The more established Canadian and New Zealand PPS legislation does, however, provide that all rights, duties and obligations arising under the Act must be exercised or discharged in good faith. Canadian case law shows that a person's failure to act in good faith has the potential to alter statutory priorities. Australia's PPS legislation does not have an equivalent good faith requirement. While recognising that commercial certainty is well-served by comprehensive statutory priority rules, this paper demonstrates that Australia's PPS legislation requires a provision enabling statutory priorities to be overridden where justified by fraud or dishonest conduct.